2017
DOI: 10.1111/nph.14902
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the enzymatic activity and physiological function of the lipid droplet‐associated triacylglycerol lipase AtOBL1

Abstract: Similar to seeds, pollen tubes contain lipid droplets that store triacylglycerol (TAG), but the fate of this TAG as well as the enzymes involved in its breakdown are unknown. Therefore, two potential TAG lipases from tobacco and Arabidopsis, NtOBL1 (Oil body lipase 1) and AtOBL1, were investigated, especially with respect to their importance for pollen tube growth. We expressed NtOBL1 and AtOBL1 as fluorescent fusion proteins to study their localization by confocal microscopy. Furthermore, we overexpressed AtO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 53 publications
(78 reference statements)
2
45
0
Order By: Relevance
“…Another enzyme we identified enriched in the LD fraction (Table 1) is a tobacco homolog of the castor bean (Ricinus communis) oil body lipase (Rc-OBL; Eastmond, 2004). Recently, we confirmed that both Nt-OBL and its Arabidopsis homolog At-OBL1 are LD-associated and that At-OBL1 is a TAG, diacylglycerol, and 1-monoacylglycerol lipase and that the activity of At-OBL1 is important for pollen tube growth (Müller and Ischebeck, 2018). We also found a previously unknown LD protein, PTLDb (Table 1, Figure 1F), and via BLAST analysis, we identified four additional tobacco homologs (Supplemental Figure 10), all of which were enriched in LD fractions isolated from tobacco pollen tubes (Supplemental Data Set 4).…”
Section: The Composition Of Lds Differs From Pollen Tubes To Seedsmentioning
confidence: 65%
See 3 more Smart Citations
“…Another enzyme we identified enriched in the LD fraction (Table 1) is a tobacco homolog of the castor bean (Ricinus communis) oil body lipase (Rc-OBL; Eastmond, 2004). Recently, we confirmed that both Nt-OBL and its Arabidopsis homolog At-OBL1 are LD-associated and that At-OBL1 is a TAG, diacylglycerol, and 1-monoacylglycerol lipase and that the activity of At-OBL1 is important for pollen tube growth (Müller and Ischebeck, 2018). We also found a previously unknown LD protein, PTLDb (Table 1, Figure 1F), and via BLAST analysis, we identified four additional tobacco homologs (Supplemental Figure 10), all of which were enriched in LD fractions isolated from tobacco pollen tubes (Supplemental Data Set 4).…”
Section: The Composition Of Lds Differs From Pollen Tubes To Seedsmentioning
confidence: 65%
“…These pollen grains contain conspicuously enlarged LDs that cannot enter the pollen tube, leading to reduced fertility. LD degradation appears to be important to some degree, as mutants disrupted in a LDassociated TAG lipase show reduced pollen tube growth (Müller and Ischebeck, 2018). Hence, while these data support the importance of LDs during pollen tube growth, it remains to be determined what specific function(s) these organelles serve.…”
Section: The Composition Of Lds Differs From Pollen Tubes To Seedsmentioning
confidence: 91%
See 2 more Smart Citations
“…Since HFA-TAG persist in developing seedlings, it is likely that Arabidopsis TAG lipases only slowly hydrolyze the storage lipid to render the FA available for growth and development. Such defective hydrolysis suggests that establishment may benefit from expression of a castor homolog of known Arabidopsis TAG lipases like SUGAR-DEPENDENT1 (Eastmond, 2006) or OIL BODY LIPASE1 (Müller and Ischebeck, 2018), based on the hypothesis that these would more rapidly hydrolyze HFA-TAG.…”
Section: Discussionmentioning
confidence: 99%